Using ChatGPT in an Instructional Design Assignment: A Study of Students’ Perceptions Based on the Model of Situated Acceptance - Proust-Androwkha, Sonia; Denis, Constance (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2025)
This article focuses on the integration of generative artificial intelligence in higher education, specifically in the form of the ChatGPT chatbot. It explores how the prescribed use of ChatGPT in an educational setting influences students’ acceptance of this technology. Based on Bobillier Chaumon’s approach of “situated acceptance” (2016) adapted to the learning context, the article analyzes technological acceptance across four dimensions: individual, interpersonal, organizational, and transpersonal. The chosen methodology is qualitative, analyzing 31 reflective accounts from students who experimented with ChatGPT during a specific educational activity conducted from December 2023 to January 2024. The results reveal varied student perceptions, emphasizing the importance of maintaining the students’ active engagement and critical thinking about emerging technologies in order to maximize the educational potential of these tools while managing the challenges they present.